Correspondence Analysis to Know Factors Related to the Use of Reducant Herbicide on Pagaralam Coffee Farmers - Irmeilyana, Irmeilyana; Ngudiantoro, Ngudiantoro; Maiyanti, Sri Indra; Febriyanti, Indrike (Pattimura International Journal of Mathematics (PIJMath), 2022)
Weed control is an attempt to care for agricultural land that can affect coffee production. This study aims to analyze the factors that have a relationship with the use of reductant herbicide in Pagaralam coffee farmers by using simple correspondence analysis. The research data included 19 variables and 3 categories of respondents based on the use of reductant herbicide, namely non-users, new users, and users. At the initial stage, each variable was carried out a mean difference test between 2 categories of respondents. Furthermore, each variable is divided into several categories. Then, by using the independence test, the categories of each variable are associated with the category of reductant use. There are 7 factors that have a relationship with the use of reductants, namely education of respondents, age of trees, length of harvest, frequency of herbicide use, frequency of chemical fertilizers used, frequency of organic fertilizers used, and number of labour outside the family (TL). The results of the correspondence analysis plot can show differences in the characteristics of the respondent's categories according to the use of reductant herbicide. The user category is dominantly characterized by having junior high school education, tree age more than 25 years, tend not to use organic fertilizer, and the harvest period can reach 3 months.